The Role of Pesantren Economic Empowerment in Fostering the Economic Self-Reliance of Santri - Siti Aminah; Agusti; Miftahus Surur (Danadyaksa: Post Modern Economy Journal, 2026)
This study aims to describe the forms of economic empowerment implemented in Islamic boarding schools (pesantren), analyze their role in promoting students' economic independence, and identify their impact on students' entrepreneurial skills and entrepreneurial mindset. The study employed a qualitative approach using a library research design combined with a case study at Salafiyah Dawuhan Islamic Boarding School, Situbondo Regency. Data were collected through documentation, limited observation, and literature review, and were analyzed using descriptive qualitative analysis involving data reduction, data display, and conclusion drawing. The findings indicate that economic empowerment is implemented in an integrated manner through the development of productive business units, student cooperatives, entrepreneurship training, and practice-based learning (learning by doing). The active involvement of students in business management enhances their entrepreneurial skills, managerial experience, sense of responsibility, self-confidence, and economic independence. Furthermore, the implementation of Islamic business ethics, such as honesty, trustworthiness (amanah), and responsibility, serves as an essential foundation for developing students with integrity and self-reliance. The economic empowerment program also contributes positively to strengthening the socio-economic relationship between the pesantren and the surrounding community. Therefore, economic empowerment in pesantren plays a strategic role in developing independent, productive, and competitive students through the integration of education, entrepreneurial practice, and Islamic values.